The Confidence Level of the Preservice Teachers: Basis for a Capability Enhancement Program - Pagodpod, Gerald F. (Asian Journal of Multidisciplinary Studies, 2024)
This study delves into an in-depth assessment of an educator's English proficiency, focusing on confidence level and psychological capacity. The preservice teachers exhibit confidence by meticulously evaluating various teaching dimensions, including lesson planning, student engagement, and technology integration. The general weighted mean across these dimensions is 3.73, indicating a high confidence level. Additionally, the preservice teachers demonstrate a robust psychological capacity, encompassing emotional intelligence and cultural competence, significantly contributing to creating a supportive and inclusive learning environment. The general weighted mean for psychological capacity is 3.83, signifying agreement. The findings underscore a substantial positive correlation between confidence level and psychological capacity, highlighting the symbiotic relationship between these factors in effective teaching. Despite the preservice teachers’ strengths, areas for improvement emerge, particularly in supporting students' emotional well-being and managing classroom behavior. These areas signal opportunities for targeted professional development interventions. Proposed capability enhancement seminars aim to refine instructional strategies, bolster emotional intelligence and cultural competence, and foster reflective practice and professional growth. By honing these skills, educators can better meet the diverse needs of their students and promote positive learning outcomes. This study emphasizes the importance of continuous professional development and self-reflection in enhancing teaching effectiveness. By addressing areas for improvement and leveraging strengths, educators can cultivate a dynamic and enriching learning environment conducive to student success in the English classroom. Recommendations for further action include implementing professional development workshops, mentorship programs, peer collaboration opportunities, cultural competence training, self-reflection practices, and utilization of support services. These initiatives can support educators in their journey toward continuous growth and excellence in teaching.